5,5’-Dithiobis (2-Nitro-Benzoic Acid)-Reactive Biomolecules in the Leaf Protoplasts of Cadmium-Exposed Eichhornia crassipes (Mart.) Solms. and Mercury-Exposed Chromolaena odorata (L.f.) R.M. King et H. Robinson - Puzon, Juliana Janet M.; Rivero, Gilda; Montano, Marco Nemesio E.; Alcantara, Hannah Joy P. (2011)
Leaf protoplasts were isolated from young and mature laminae of Eichhornia crassipes (Mart.) Solms. and Chromolaena odorata (L.f.) R.M. King et H. Robinson exposed to 5.00 ppm CdCl 2 and 1.00 ppm Hg(NO 3) 2, respectively, in Hoagland nutrient hydroponic systems for 7 d. Cd 2+ and Hg 2+ accumulated in the protoplasts of E. crassipes and C. odorata plants, respectively, based on the results of inductively coupled plasma-atomic emission spectrophotometry (ICP-AES). Heavy metal-binding peptides containing sulfhydryl (SH) were extracted from the isolated protoplasts through gel column chromatography and were detected through reactivity with Ellman's reagent, 5,5'-dithiobis (2-nitro-benzoic acid), or DTNB. Levels of DTNB-reactive peptides, as well as S-metal complexes and S 2-, were remarkably higher in the leaf protoplasts of Cd-exposed E. crassipes and Hg-exposed C. odorata compared with the protoplasts of the control plants. In the heavy metal-exposed plants, the young protoplasts accumulated higher levels of Cd 2+ and Hg 2+, with a concomitant increase in S 2- content, S-metal complexes and DTNB-reactive peptides compared with the mature protoplasts. These results suggest that young cells are more capable of coping with Cd and Hg toxicity. There was a marked increase in levels of DTNB-reactive, heavy metal-binding peptides in the leaf protoplasts as a biochemical mechanism for Cd and Hg tolerance in E. crassipes and C. odorata, respectively.
Keywords: Plant morphology; Chemical reactions